Penerapan Kebijakan tentang Peraturan Daerah Nomor 7 Tahun 2017 di Kabupaten Buleleng - Nyoman Doddy Darmawan; Nyoman Diah Utari Dewi; Luh Riniti Rahayu (Penerbit Goodwood, 2023)
Purpose: to find out the implementation, constraints, and efforts in implementing Buleleng Regency Regional Regulation No. 7 of 2017 concerning TJSLP in Buleleng Regency. Method: The instrument used in this study is the interview guideline. Researchers used Miles and Huberman's interactive model to analyze the research data Result: The implementation of Buleleng Regency Regional Regulation No. 7 of 2017 concerning TJSLP in Buleleng Regency has not run optimally, Obstacles when implementing Buleleng Regency Regional Regulation No. 7 of 2017 concerning TJSLP in Buleleng Regency include no commitment from the leadership so that the officers below do not carry out their duties optimally, and efforts are made to overcome obstacles in implementing Buleleng Regency Regional Regulation No. 7 2017 regarding TJSLP in Buleleng Regency among others is that the local government will invite companies to coordinate and agree on regional priority programs/activities that can be realized through TJSLP Limitation: This study only used a few informants, so future research may consider using more informants.